2021
DOI: 10.7759/cureus.13684
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Mortality in Patients After Oncologic Gastrointestinal Surgery: Comparison of the ASA, APACHE II, and POSSUM Scoring Systems

Abstract: Scoring systems have been developed to predict the expected mortality and morbidity in surgical procedures. In this study, our aim was to compare the ASA (American Society of Anesthesiologists), APACHE (Acute Physiology and Chronic Health Evaluation) II, POSSUM (Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity) scoring systems as predictors of mortality in patients who underwent gastrointestinal oncologic surgery, followed, and were admitted to the intensive care unit d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…This is in concordance with a study published by Kisa N.G. et al which found that in patients undergoing oncological gastrointestinal surgery the APACHE II score and the P-POSSUM score are more reliable than the ASA scoring system in predicting mortality [35].…”
Section: Discussionsupporting
confidence: 93%
“…This is in concordance with a study published by Kisa N.G. et al which found that in patients undergoing oncological gastrointestinal surgery the APACHE II score and the P-POSSUM score are more reliable than the ASA scoring system in predicting mortality [35].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, in our study, the AUC-ROC value obtained using the nomogram constructed by Zhou (12) was 0.663 in the training set and 0.662 in the testing set. When the AUC-ROC is <0.700, the discriminative power of the test is not statistically significant (26)(27)(28). The other nomogram comprised three variables: AF, NIHSS scores, and glucose level (17).…”
Section: The Training Setmentioning
confidence: 99%
“…[3,7] Regarding the scores obtained from the different scales, they were significantly different between patients who died or experienced morbidity and patients who did not die or did not develop morbidity within 30 days postoperatively, as observed in the literature. [12,13] This implies that patients who experienced morbidity or mortality had distinct scoring patterns compared to those who did not experience such outcomes. In terms of calibration, all scales demonstrated good ability to predict the occurrence of morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%